VisualChat: a visualization tool for human-machine interaction - Goh, Ong Sing; Fung, C.C.; Wong, K.W. (IEEE, 2008)
This paper proposes a technique to analyze and visualize the human-machine interaction corpus using VisualChat. The evaluation used in this study is based on real-time interaction between machines or software robots called AINI (Artificial Intelligent Natural Language Identity) and online human user using MSN messenger, a Web-based messaging system called MSNChat. The result shows that VisualChat is a useful tool to evaluate the human-machine interaction corpus.